2013
DOI: 10.1088/0957-0233/24/7/075401
|View full text |Cite
|
Sign up to set email alerts
|

Image reconstruction method of electrical capacitance tomography based on compressed sensing principle

Abstract: To improve the image reconstruction quality of electrical capacitance tomography (ECT), a new ECT image reconstruction method based on compressed sensing principle is proposed. The capacitances’ collection of the ECT system is regarded as linear measurement of compressed sensing; the measurement matrix is designed by randomly realigning the row vectors of a new sensitivity matrix, which is reconstructed by zero vectors’ expansion of the original sensitivity matrix, and the capacitance vectors expanded in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The main process of CS is the linear measurement, where a highdimensional signal x is projected to a low-dimensional measurement vector y using a measurement matrix Φ [22]. This process can be expressed as follows:…”
Section: Mathematical Model Of Ect Based On Csmentioning
confidence: 99%
See 1 more Smart Citation
“…The main process of CS is the linear measurement, where a highdimensional signal x is projected to a low-dimensional measurement vector y using a measurement matrix Φ [22]. This process can be expressed as follows:…”
Section: Mathematical Model Of Ect Based On Csmentioning
confidence: 99%
“…At present, reconstruction methods based on the CS theory have been extended for ECT image reconstruction [13,[19][20][21][22][23][24], and the grey-value vector of the image to be reconstructed is transformed into a sparse signal usually by a sparse transform [21][22][23][24]. However, the signal sparsity before and after the sparse transform is not compared, and the fidelity of the sparse signal obtained after the sparse transform to the original signal under different sparsity degrees is not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous inversion algorithms were suggested for ECT image reconstruction [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. However, due to the Ill-posedness, Ill-conditioning and Non-linearity of the ECT problem, the quality of the reconstructed images is still under research for enhancement.…”
Section: Limited Region Tomography (Lrt)mentioning
confidence: 99%
“…They showed that the method can produce fairly high quality reconstructions with clear edges and high precision. Another work by Wu et al [29] explored the EVT image reconstruction problem based on Compressive Sensing principles. The permittivity distribution of some object inside a pipeline was recovered by Orthogonal Matching Pursuit algorithm.…”
Section: Related Workmentioning
confidence: 99%